Video reflection in literacy teacher education and development lessons from research and practice - Ortlieb, Evan; McVee, Mary B.; Shanahan, Lynn E. (Emerald, 2015)
Within the field of education there is a growing body of research focused on the use of video as a mediational tool for reflection. The purpose of this volume is to bring together research and research-based practices from wide array of literacy scholars and practitioners who are using video in educational research and/or teaching and for the purposes of reflection. This volume will recruit authors internationally to provide a cutting edge treatment of video reflection as pertaining to literacy education. We seek educators including individuals involved with: teacher education, professional development, classroom teaching, evaluation, literacy practicums, centers and clinics or other educational settings. Inter-disciplinary chapters (e.g., science and literacy, the arts and literacy) are also welcome.
Keywords: Education -- General.; Teachers' classroom resources & material.; Reading teachers -- Training of.; Visual education.; Literacy -- Study and teaching.; elektronické knihy; electronic books